Predominance of blaCTX-M-65 and blaCTX-M-55 in extended-spectrum β-lactamase-producing Escherichia coli from raw retail chicken in South Korea. (June 2019) - Park, Hyeeun; Kim, Jinshil; Ryu, Sangryeol; Jeon, Byeonghwa
Highlights: First characterisation of extended-spectrum β-lactamase-producing E. coli (ESBL-EC) from raw retail chicken in South Korea. bla CTX-M-65 was the predominant ESBL gene in ESBL-EC isolates from chicken. Multidrug resistance is highly common in ESBL-EC from retail chicken in South Korea. ESBL-EC isolates from retail chicken in South Korea possess virulence genes of extraintestinal pathogenic E. coli (ExPEC). Abstract: Objectives: Extended-spectrum β-lactamase-producing Escherichia coli (ESBL-EC) are a serious public health concern worldwide. The aim of this study was to characterise ESBL-EC isolated from raw retail chicken in South Korea. Methods: The antimicrobial resistance, phylogenetic group and virulence gene prevalence of 67 ESBL-EC isolated from retail chicken in South Korea were investigated. Results: All of the isolates possessed bla CTX-M genes, predominantly bla CTX-M-65 (52.2%) and bla CTX-M-55 (25.4%), and three isolates harboured both bla CTX-M-65 and bla CTX-M-55 . More than one-half of the ESBL-EC strains also carried bla TEM . Antimicrobial susceptibility testing revealed that 98.5% of the strains were multidrug-resistant (MDR). Phylogenetic analysis showed that group A was predominant (56.7%), followed by B1 (19.4%), E (8.9%), B2 (6.0%) and D (6.0%). Virulence genes associated with extraintestinal pathogenic E. coli (ExPEC) were frequently detected in isolates of phylogenetic groups B1, B2, D and E. Conclusion: The results in this study demonstrate that retail chicken in South Korea is highly contaminated with MDR ESBL-EC and may serve as a reservoir for transmitting ExPEC to humans.